12x=6x+3

Simple and best practice solution for 12x=6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x=6x+3 equation:


Simplifying
12x = 6x + 3

Reorder the terms:
12x = 3 + 6x

Solving
12x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
12x + -6x = 3 + 6x + -6x

Combine like terms: 12x + -6x = 6x
6x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
6x = 3 + 0
6x = 3

Divide each side by '6'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| -7+9h=8h | | -62=7x+8 | | 3w+7=4w+13 | | 5x/3=11 | | 2x+y-4(x+2y)=13-2(3y-x)+y | | 3y+8=8y-8 | | f(x)=x^4+5x^2+6 | | 4=7x+8 | | 1+1k=1+1k | | 2(x+y)-4(x+y)=8(x+2)-8(y-2) | | 9y^2+37y+9= | | 8x+5=3x+38 | | 6=-6x+3y | | 6=-6+3x | | (9+8n)+(-4-3n)+(3+6n)= | | C-u=n+t | | 3n+4=32-4n | | 6=6x+3y | | -20+(20d)=100 | | 5-4+7x+1=6x+9 | | 1/3=4/g | | 7x+16=2(8x+1)-4 | | A=3b-cx | | 14x+1=78 | | 1y+2y+3y=42 | | 24x=-23 | | 9b-6=6b | | 4z+5=5z-1 | | 3y=2z+8solvez | | -30-4n=9n-9 | | 12=2x-17 | | 18w+30=20w+20 |

Equations solver categories